Disrupting Bordetella Immunosuppression Reveals a Role for Eosinophils in Coordinating the Adaptive Immune Response in the Respiratory Tract - Monica C. Gestal; Uriel Blas-Machado; Hannah M. Johnson; Lily N. Rubin; Kalyan K. Dewan; Claire Bryant; Michael Tiemeyer; Eric T. Harvill (Microorganisms, 2020)
Recent findings revealed pivotal roles for eosinophils in protection against parasitic and viral infections, as well as modulation of adaptive immune responses in the gastric mucosa. However, the known effects of eosinophils within the respiratory tract remain predominantly pathological, associated with allergy and asthma. Simulating natural respiratory infections in mice, we examined how efficient and well-adapted pathogens can block eosinophil functions that contribute to the immune response. Bordetella bronchiseptica, a natural pathogen of the mouse, uses the sigma factor btrS to regulate expression of mechanisms that interfere with eosinophil recruitment and function. When btrS is disrupted, immunomodulators are dysregulated, and eosinophils are recruited to the lungs, suggesting they may contribute to much more efficient generation of adaptive immunity induced by this mutant. Eosinophil-deficient mice failed to produce pro-inflammatory cytokines, to recruit lymphocytes, to organize lymphoid aggregates that resemble Bronchus Associated Lymphoid Tissue (BALT), to generate an effective antibody response, and to clear bacterial infection from the respiratory tract. Importantly, the failure of eosinophil-deficient mice to produce these lymphoid aggregates indicates that eosinophils can mediate the generation of an effective lymphoid response in the lungs. These data demonstrate that efficient respiratory pathogens can block eosinophil recruitment, to inhibit the generation of robust adaptive immune responses. They also suggest that some post-infection sequelae involving eosinophils, such as allergy and asthma, might be a consequence of bacterial mechanisms that manipulate their accumulation and/or function within the respiratory tract.